Trifluoperazine-Induced Cholestatic Jaundice - Sharifi, Vandad (Tehran University of Medical Sciences, 2010)
Liver injury occurs with many drugs; therefore, a thorough work up is important for establishing the diagnosis. We report a case of trifluoperazine-induced cholestatic jaundice. A 44-year old male with schizoaffective disorder developed an increase in liver enzymes and jaundice after starting treatment with trifluoperazine. Workup for other potential etiologies was negative.